Synthesis and characterization of glass-ceramic sponge from borosilicate waste glass - Firas J. Hmood (Cerâmica)
Abstract Glass-ceramic sponges are promising structures for many technical applications. This work deals with the preparation and characterization of porous glass-ceramic using borosilicate glass waste. The particle size distribution of Pyrex waste glass used in this study was d10:42, d50:10, and d90:2 µm. Cubic samples of 1 cm3 were shaped using the replica method. A polyurethane sponge of 25 ppi was employed as a print back for the glass-ceramic sponge. A suspension of 70% solid loading was prepared for the replication. The samples were firstly annealed at 450°C for 1 h to burn out the polyurethane sponge. Then, the temperature was raised to 650, 700, and 750°C, respectively, to enhance the strength of samples. The results revealed that the density of sintered bodies at 750 °C was 0.47 g/cm3, which represents the highest value of density reached. Moreover, the fabricated glass-ceramic sponges revealed sintering temperature-dependent properties. For instance, samples sintered at 750 ºC showed compressive strength of 0.145 ± 0.15 MPa corresponding to 65% porosity.